The Role of Foreign Language Learners’ Self- Esteem in Enhancing Their Oral Performance - BOUCHAREB, Naouel (Journal of Human Sciences, 2016)
Nowadays, the affective side of learners receives a noticeable attention in the learning process, mainly personality factors. The present study aims to explore the relationship between Algerian second year LMD Students of English as foreign language’ self-esteem level and their oral production at the University of Constantine 1, Algeria. The hypothesis states that the more Algerian second year students of English, at the University of Constantine 1, trust their abilities, the more they will be able to enhance their English speaking performance. The research work is mainly concerned with finding whereby the feeling of “I am able to do it” has any relation with learners’ oral production. The research methodology adopted in this study is a descriptive one. It intends to describe two variables: self-esteem as the supposed independent variable and foreign language speaking as the assumed dependent variable, and to identify the relationship between them. Data were gathered through a series of questionnaires administered to a random sample of 30 Algerian second year LMD students and delivered to 10 teachers of Oral Expression, both at the English Department, University of Constantine 1. The results obtained from the present research show that there is a positive relationship between students’ self-esteem and their foreign language speaking performance, and that this relationship affects directly their level of academic achievement, in general. Furthermore, on the light of this study, it is possible to put forward that a learner is his /her real judge in learning a foreign spoken language. Overall, the results obtained lead us to suggest that learners must pay more attention to their self-esteem for better oral performance.